An Integrative Approach to Neuroinflammation in Psychiatric disorders and Neuropathic Pain. (August 2018) - Lurie, Diana I
Neuroinflammation is a complex process involving both the peripheral circulation and the Central Nervous System (CNS) and is considered to underlie many CNS disorders including depression, anxiety, schizophrenia, and pain. Stressors including early-life adversity, psychosocial stress, and infection appear to prime microglia toward a pro-inflammatory phenotype. Subsequent inflammatory challenges then drive an exaggerated neuroinflammatory response involving the upregulation of pro-inflammatory mediators that is associated with CNS dysfunction. Several pharmacologic inhibitors of pro-inflammatory cytokines including TNF-α and IL-1β show good clinical efficacy in terms of ameliorating neuroinflammatory processes. Mind/body and plant-based interventions such as yoga, breathing exercises, meditation, and herbs/spices have also been demonstrated to reduce pro-inflammatory cytokines and have a positive impact on depression, anxiety, cognition, and pain. As the intricate connections between the immune system and the nervous system continue to be elucidated, successful therapies for reducing neuroinflammation will likely involve an integrated approach combining drug therapy with nonpharmacologic interventions.